Estimates of temporal-spatial variability of wildfire danger across the Pan-Arctic and extra-tropics. (12th April 2021) - Justino, Flavio; Bromwich, David; Wilson, Aaron; Silva, Alex; Avila-Diaz, Alvaro; Fernandez, Alfonso; Rodrigues, Jackson
Abstract: Satellite-based hot-spot analysis for the Pan-Arctic, shows that Asia experiences a greater number of fires compared to North America and Europe. While hot spots are prevalent through the year in Asia, Europe (North America) exhibits marked annual (semi-annual) variability. The Potential Fire Danger index (PFIv2) demonstrates increased fire incidence vulnerability across the Arctic and extra-tropics. Though not significant in northwestern North America and eastern Asia, significant-positive trends across the mid-latitudes of Eurasia and Siberia are clear. PFIv2 accurately matches the regional distribution of observed fires, while the worldwide used Fire Weather Index does not. Fire danger has evolved as distributions of short-interval precipitation events and background vegetation characteristics change. In conjunction with increased population and expanded infrastructure, frequent extreme events may increase pressure for new settlements that lead to greater fire exposure across the Pan-Arctic. Thus, PFIv2 may be useful for decision planners and danger managers to anticipate and minimize the adverse effects of indiscriminate fire use.